Impact of Heavy Metals (Zinc and Copper) on the Survival Rate and Reproductive Behaviour of Earthworm (Eisenia Fetida) - Zafar , Amina; Akhtar, Amara; Noreen , Ayesha (Indus Journal of Bioscience Research, 2025)
Earthworms play a crucial role in maintaining soil health by enhancing fertility through their burrowing, nutrient recycling and organic matter decomposition. Their ecological functions disrupted by environmental stresses particularly heavy metal contamination from elements like Zinc (Zn) and Copper (Cu). This study aimed to assess the impact of heavy metals on earthworms and their ability to accumulate Zn and Cu. Earthworms were collected from different agricultural sites and maintained under laboratory conditions for a period of 28 days. Four experimental groups were established. The control group (T0) received no exposure to heavy metals, whereas the treatment groups (T1, T2, and T3) were subjected to increasing concentrations of Zinc (Zn) at 1.5 mg/kg, 2.0 mg/kg, and 2.5 mg/kg and Copper (Cu) at 0.1 mg/kg, 0.2 mg/kg, and 0.3 mg/kg, respectively. Prior to the experiment, all earthworms underwent a one-week acclimatization period in soil trays and were provided with a standard feed. Key parameters assessed included total body weight, length, biomass, cocoon production and population changes. A significant reduction in growth was observed in group T3 (1.098 ± 0.030) reflecting high variability when compared with the other treatments. Survival rates were lowest in T3, where only 5 earthworms survived, while the highest survival was recorded in the control group (T0), where all 15 earthworms remained alive. Cocoon production also declined in T3, with only 2 cocoons produced compared to 8 in the control group. Data were statistically analyzed using one-way ANOVA. Growth and survival rates showed significant declines (P < 0.05), indicating that exposure to higher metal concentrations adversely affected these parameters. However, reproductive output showed no statistically significant difference (P > 0.05).